Autophagy-Related Activation of Hepatic Stellate Cells Reduces Cellular miR-29a by Promoting Its Vesicular SecretionSummary - Xiaojie Yu; Natalia Elfimova; Marion Müller; Daniel Bachurski; Ulrike Koitzsch; Uta Drebber; Esther Mahabir; Hinrich P. Hansen; Scott L. Friedman; Sabine Klein; Hans Peter Dienes; Marianna Hösel; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2022)
Background & Aims: Liver fibrosis arises from long-term chronic liver injury, accompanied by an accelerated wound healing response with interstitial accumulation of extracellular matrix (ECM). Activated hepatic stellate cells (HSC) are the main source for ECM production. MicroRNA29a (miR-29a) is a crucial antifibrotic miRNA that is repressed during fibrosis, resulting in up-regulation of collagen synthesis. Methods: Intracellular and extracellular miRNA levels of primary and immortalized myofibroblastic HSC in response to profibrogenic stimulation by transforming growth factor β (TGFβ) or platelet-derived growth factor-BB (PDGF-BB) or upon inhibition of vesicular transport and autophagy processes were determined by quantitative polymerase chain reaction. Autophagy flux was studied by electron microscopy, flow cytometry, immunoblotting, and immunocytochemistry. Hepatic and serum miR-29a levels were quantified by using both liver tissue and serum samples from a cohort of chronic hepatitis C virus patients and a murine CCl4 induced liver fibrosis model. Results: In our study, we show that TGFβ and PDGF-BB resulted in decrease of intracellular miR-29a and a pronounced increase of vesicular miR-29a release into the supernatant. Strikingly, miR-29a vesicular release was accompanied by enhanced autophagic activity and up-regulation of the autophagy marker protein LC3. Moreover, autophagy inhibition strongly prevented miR-29a secretion and repressed its targets’ expression such as Col1A1. Consistently, hepatic miR-29a loss and increased LC3 expression in myofibroblastic HSC were associated with increased serum miR-29a levels in CCl4-treated murine liver fibrosis and specimens of hepatitis C virus patients with chronic liver disease. Conclusions: We provide evidence that activation-associated autophagy in HSC induces release of miR-29a, whereas inhibition of autophagy represses fibrogenic gene expression in part through attenuated miR-29a secretion.